Rural banking in Nigeria - Osuntogun, C. Adeniyi; Adewunmi, Wole.; Nigerian Institute of Bankers (Burnt Mill, Harlow, Essex, UK : Longman ; [Lagos?] : Nigerian Institute of Bankers, 1983)
This book analyses the hitherto limited operations of commercial banks in the rural sector and points to the urgent need for an enlargement of their services. There is also a valuable comparative study of the rural banking experience in India
Selected papers from a seminar sponsored by the Nigerian Institute of Bankers and held at the University of Ife, Ife, Nigeria, Mar. 29-Apr. 1, 1979.
Includes bibliographies and index.
osc 22/9/17
Loans
Keywords: Banks and banking; Agricultural credit; Rural development; Agricultural extension work